2017
DOI: 10.1016/j.kjms.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Educational intervention on physical restraint use in long‐term care facilities – Systematic review and meta‐analysis

Abstract: A systematic review with meta-analysis and meta-regression. Eight databases, including Cochrane Library, ProQuest, PubMed, EMBASE, EBSCO, Web of Science, Ovid Medline and Physiotherapy Evidence Database (PEDro), were searched up to January 2017. Eligible studies were classified by intervention and accessed for quality using the Quality Assessment Tool for quantitative studies. Sixteen research articles were eligible in the final review; 10 randomize control trail studies were included in the analysis. The meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 39 publications
6
43
0
2
Order By: Relevance
“…Disagreements and discrepancies were resolved by consensus, and when necessary, by consultation and discussion within the reviewer teams during all stages of the review process (Federica Canzan, Luigina Mortari, Luisa Saiani and Elisa Ambrosi). Risk bias of randomized controlled trials (RCTs) was assessed according to the Cochrane Handbook for Systematic Reviews of Interventions [24]. For RCTs, we considered random sequence generation, allocation concealment, blinding of participants and personnel, blinding of outcome assessment, incomplete outcome data, selective outcome reporting, and other bias.…”
Section: Quality Appraisalmentioning
confidence: 99%
See 2 more Smart Citations
“…Disagreements and discrepancies were resolved by consensus, and when necessary, by consultation and discussion within the reviewer teams during all stages of the review process (Federica Canzan, Luigina Mortari, Luisa Saiani and Elisa Ambrosi). Risk bias of randomized controlled trials (RCTs) was assessed according to the Cochrane Handbook for Systematic Reviews of Interventions [24]. For RCTs, we considered random sequence generation, allocation concealment, blinding of participants and personnel, blinding of outcome assessment, incomplete outcome data, selective outcome reporting, and other bias.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…For one study further detail have been requested about the data and effect size about PR used [26]. To assess statistical heterogeneity, we calculated the I 2 using Review Manager 5.3 (RevMan, Copenhagen, Denmark); the primary analysis used a random-effects model (risk ratio, RR), which had the highest generalizability in our empirical examination of summary effect measures for meta-analyses [24]. If the heterogeneity with random-effect model was I 2 < 50% we used fixed model to estimate the intervention effects, in contrast, if I 2 > 50% we used random-effect model.…”
Section: Synthesis and Supplementary Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Several countries started to carry out legislative efforts that aim to control or reduce the utilization of coercive measures in clinical psychiatric settings and started to emerge to control the use of these measures in many countries 13 . However, in the professional psychiatric literature, it was found that legislative and policy changing is inadequate in terms of reducing the incidence of using coercion toward psychiatric patients 14 . However, in this regard, one might say that healthcare providers should be encouraged to create or design treatment culture that emphasizes the use of least restrictive measures or alternatives when dealing with aggressive psychiatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are inconsistent; no clear association has been identified. A comparative survey in three countries showed that the nurses 'attitudes differ depending on the nurses' definition of physical restraint and their national and cultural affiliation (Lan S H et al, 2017).…”
Section: Introductionmentioning
confidence: 99%